The Role of Social Media in Supporting Character Education Programs: An Analysis of Integrated Curriculum Management in the Digital Era - Romi Mesra; Paulus Robert Tuerah; Theodorus Pangalila; Veronike E.T Salem; Manuel Vidi Korompis (PT. NALURI EDUKASI PRESS, 2024)
This study aims to analyze the role of social media in supporting character education programs through integrated curriculum management in the digital era. The method used is a qualitative approach with a focus on a systematic literature review, involving thematic analysis of various academic sources and current policies. The results of the study indicate that the integration of social media in the character education curriculum can increase student engagement, develop critical thinking skills, and facilitate cross-cultural collaborative learning. However, effective implementation requires adaptive curriculum management, development of teacher digital competencies, and policies that balance the use of technology with student security and privacy. This study concludes that an integrated approach to integrating social media into character education has significant potential to prepare students to face ethical challenges in the digital era.